2006
DOI: 10.1111/j.1439-0523.2006.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of generation means and components of variance for parthenocarpy in cucumber (Cucumis sativus L.)

Abstract: Parthenocarpy (seedless fruit) has potential for increasing yield in cucumber (Cucumis sativus var. sativus L.). To determine the inheritance of parthenocarpy in gynoecious cucumber, generations derived from crossing two nonparthenocarpic gynoecious inbred lines [Gy8 (P 2 ; processing type) and ÔMarketmore 80Õ (P 2 ; MM, fresh market type)] with a highly parthenocarpic inbred line [2A (P 1 ; processing type)] were evaluated for fruit number in a greenhouse at Arlington, Wisc. in 1999 (designated 2A · Gy8 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…However, the F 1 progeny mean in G-block was lower than the mid-parent value (Table 3). Although openfield experiments were conducted for only one year, results confirmed an earlier finding from a generation means analysis of cross progeny derived from P 1 and P 2 (Sun et al 2006a) that demonstrated that genotype performances vary across growing environments. Under dissimilar experimental conditions differences in magnitude (not in rank) between treatments would be expected given the environmental influence on parthenocarpic fruit development.…”
Section: Generation Meanssupporting
confidence: 87%
“…However, the F 1 progeny mean in G-block was lower than the mid-parent value (Table 3). Although openfield experiments were conducted for only one year, results confirmed an earlier finding from a generation means analysis of cross progeny derived from P 1 and P 2 (Sun et al 2006a) that demonstrated that genotype performances vary across growing environments. Under dissimilar experimental conditions differences in magnitude (not in rank) between treatments would be expected given the environmental influence on parthenocarpic fruit development.…”
Section: Generation Meanssupporting
confidence: 87%
“…No research of this type has been previously performed in L. acuteangula. Inheritance of fruit shape, fruit size, and color in C. sativa has been reported (Sun et al, 2006). Ahmed et al (2003) reported the importance of nonadditive gene action for vegetative characters and the importance of additive and nonadditive gene action for total fruit number and precocious production of summer squash (C. pepo L.).…”
Section: Resultsmentioning
confidence: 96%
“…Inheritance of fruit quality traits has been reported in previous study (Umaharan et al, 1997;Lavi et al, 1998;Zalapa et al, 2006;Sun et al, 2006), but these efforts do not contain the maternal plant effect. The nutrition for fruit composed of carpodermis, pulp and seed was supported by maternal plant.…”
Section: Discussionmentioning
confidence: 99%